Spider Parental Care and Awe-Inspiring Egg Sac (Cocoon) - Ewunkem, Akamu Jude; Agee, Kyle (International Journal of Zoology, 2022)
Spiders (Arachnida, Araneae) represent one of the largest groups of organisms on Earth with more than 45,000 recorded species found in nearly all terrestrial communities. In these communities, spiders are obligate predators and generalist consumers regulating the density of pests. Spiders have a stupefying array of prey hunting strategies ranging from ambushing to the use of complex silk nares. Spider silk is incredibly tough and can be used for many applications such as wrapping and immobilization, catching prey, as dragline to connect spiders to the web, as ballooning to aid dispersal of juveniles, as shelters in burrows, for mating, and as egg sacs (or cocoons). Typically, spider egg sacs are multilayered, complex structures that physically protect the eggs and hatchlings against parasitoids, predators as well as changing temperatures. Much research has been undertaken to elucidate the ecological role of spiders and the mechanical characteristics of silks. However, few studies have examined the parental care of spiders and the role of egg sacs. This review goes into great detail about spider parental care and the functions of egg sacs.